A9 MUCUS BARRIER INTEGRITY IS IMPAIRED BY A DYSFUNCTIONAL MESENCHYME. (1st March 2018) - Reyes-Nicolas, V; Allaire, J M; Ouellet, C; Servant, R; Pomerleau, V; Garde-Granger, P; Boudreau, F; Perreault, N
Abstract: Background: A mucus layer separates gut bacteria from the host epithelium. Changes in mucus properties, mucins production and maturation, are affected in IBD. Our results have previously shown that without an inflammatory stress, Bmpr1a △MES mice presented colon crypt distortion, polyposis at 1 year and immune cells infiltration. At 90 days, loss of mesenchymal Bmps signaling impairs the goblet cells vesicles composition as well as the fucosylation process. This indicated that the loss of Bmps signaling in myofibroblasts produces an impairment of mucus maturation, consequently might impact on the susceptibility to ulcerative colitis in the mutant mice. Aims: We propose to address whether mesenchymal Bmps signaling contributes to the barrier function of colon mucus and influences the severity of the inflammation Methods: Colitis was induced in mice by DSS using two strategies: 7 days acute injury and acute injury followed by 14 days of recovery. Tissue structures were studied by H&E staining. Immunostaining was performed against collagen I, IV and fibronectin. Colons were fixed in Carnoy solution and luminal mucus layers were observed by Alcian blue staining before and after treatments. In addition, bacteria infiltration was evaluated by FISH using the general bacterial rRNA probe, EUB338 conjugated with Cy3. Goblet cells maturation and functionality genes Fut2, Muc2, Tff3, and Klf4 were analyzed by qPCR. Results: DAI and morphological analysis indicated that Bmpr1a △MES mice exhibited increased susceptibility to experimental colitis and presented an important delay in the healing process. An increase in deposition of ECM proteins, reminiscence of fibrosis, was found in Bmpr1a △MES mice compare to controls. Before treatment, Bmpr1a △MES mice presented a thinner and discontinuous inner mucus layer compared to control mice. After treatments, a partial erosion of the inner mucus layer occurred in all mice but was advanced in Bmpr1a △MES . Bacteria were only detected in the outer mucus layer of the distal colon in control mice, whereas in native Bmpr1a △MES mice, bacteria were found within the inner mucus layer and close to the non-inflamed epithelium. Following DSS treatment, bacteria were seen in contact with the epithelia in control mice, while large amounts of bacteria were found invading colonic tissue in Bmpr1a △MES mice. Finally, differential expression of goblets cells genes maturation and functionality was found between groups. Conclusions: Our results reveal that Bmpr1a △MES mice increased sensitivity to experimental colitis. These findings suggest an abnormal goblet cells maturation which fails to produce a functional mucus barrier and allows bacteria to penetrate the epithelium. Also, it suggests that mesenchymal Bmps signaling could be a potential key component in the healing process. Funding Agencies: CIHRScholarship Centre de Recherche Médicale de l'Université de Sherbrooke (CRMUS)